Analysis of child development based on development psychological theory - Tanjung, Romi Fajar; Sucipto, Sigit Dwi; Lubis, Khadijah; Suryani, Yuni Dwi; Minarsi, Minarsi (Journal of Education and Learning (EduLearn), 2024)
Children are unique humans and experience varied development even though they are of the same gene or the same sex but grow and develop according to their respective characteristics. Of course, this condition also demands adjustments in providing appropriate and varied stimuli and responses. This study aims to observe the growth and development of children to explore the growth and development of children and see the reactions generated by children if given a specific stimulus. This research method uses longitudinal case studies. The respondents of this study were three children. The study found that children's cognitive, psychosocial and moral development can be developed by conditioning the child and the child's environment. Children's health and a conducive environment play an essential role in determining children's growth and development. Maternal health and parental cooperation also determine the growth and development of the child.